EMPLOYER’S LIABILITY IN SERBIA FOR DAMAGE CAUSED BY WORK INJURY: THE CASE OF PROFESSIONAL ATHLETES - Petrović, Mila D (Pravni zapisi, 2023)
The right to safety and health at work is one of the fundamental human rights at work, which is protected by the highest international and national legal instruments. In Serbian law, such a right is protected, firstly, by the Constitution of the Republic of Serbia itself and then, further, through the Labour Law and the Law on Safety and Health, whose norms address this issue more thoroughly. These norms are embodied first and foremost in certain obligations of employers, with the aim of ensuring safety and health at work primarily for their employees. In cases where the employer fails to provide a safe and healthy work environment, or even when an injury happens despite everything in this process being done correctly, the question of the employer’s liability for the damage which was caused at work arises. This paper provides an analysis of this issue, with emphasis on the issue of liability for the damage thus caused to the athletes with an employee status.
Keywords: safety and health at work; injury at work; employer's liability; professional athletes; sport; Republic of Serbia